Analisis Larangan Pencatatan Perkawinan Beda Agama Dalam Sema Nomor 2 Tahun 2023: Sebuah Tinjauan Dari Perspektif Hak Asasi Manusia - Amisah, Amisah; Hadiati, Mia (UNES Law Review, 2024)
Interfaith marriage are still a hot topic of discussion among Indonesian society, to overcome this problem the Supreme Court (MA) issued SEMA Number 2 of 2023 which contains a prohibition on the Courts not to approve applications for registration of interfaith marriages. This research aims to determine the Human Rights perspective on SEMA Number 2 of 2023, by applying normative juridical methods, and library research as a technique in collecting data. The results of this study show that SEMA Number 2 of 2023 has drawn pros and cons, from a human rights perspective, the prohibition in SEMA Number 2 of 2023 is considered discriminatory and not in line with human rights principles, which ignores the freedom to practice religion and guarantee the protection of marriage rights without religious restrictions as stated in Article 3 paragraph (3) of Law Number 39 of 1999 concerning Human Rights, Article 28 E paragraph (1) and Article 29 paragraph (2) of the 1945 Constitution, Article 16 paragraph (1) of the Universal Declaration of Human Rights (UDHR), Article 2 paragraph (1) and Article 23 paragraph (2) of the International Covenant on Civil and Political Rights.